Building interactive worlds in 3D : - Gauthier, Jean-Marc (Elsevier, 2005)
Coming at the process of making interactive worlds from a non-gaming viewpoint proves to be a refreshing break...Provided is a version of the Virtools pre-visualisation package, which is used to set up the interaction between objects, cameras and players. And this is where Gauthier comes into his own with paticularly thought-provoking chapters on issues such as camera set-up and pathfinding